PENGARUH KARAKTERISTIK KEWIRAUSAHAAN TERHADAP NIAT BERWIRAUSAHA PADA MAHASISWA FAKULTAS EKONOMI UNISRI DENGAN MOTIVASI BERWIRAUSAHA SEBAGAI VARIABEL MODERASI - William Sumanjaya, Erni Widajanti & Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this study was to analyze: 1) the effect of entrepreneurial characteristics on student’s entrepreneurship intentions 2) the effect of entrepreneurship motivation on student’s entrepreneurship intention, and 3) the effect of entrepreneurial characteristics on student’s entrepreneurship intenton with on the entrepreneurship motivation as a moderating variable. This study is a survey. The study population were students of the Faculty of Economics Slamet Riyadi University Surakarta in years 2012 and 2013. The research sample 59 used purposive sampling then used proportional cluster random sampling technique. The technique of collecting data used interviews, questionnaires and observations. Data were analyzed using the research instrument test, classic assumption test, multiple linear regression analysis, t-test, F, coefficient determination and test the absolute difference. The results showed that entrepreneurial characteristics has significant effect on student’s entrepreneurship intention. Entrepreneurship motivation has significant effect in students influence the entrepreneurship intention. Entrepreneurship motivation does not moderate effect of on entrepreneurial characteristics on student’s entrepreneurship intention.Keywords: entrepreneurial characteristics, entrepreneurship motivation, entrepreneurship intention.